2009
DOI: 10.1261/rna.1705309
|View full text |Cite
|
Sign up to set email alerts
|

Complex architecture and regulated expression of the Sox2ot locus during vertebrate development

Abstract: The Sox2 gene is a key regulator of pluripotency embedded within an intron of a long noncoding RNA (ncRNA), termed Sox2 overlapping transcript (Sox2ot), which is transcribed in the same orientation. However, this ncRNA remains uncharacterized. Here we show that Sox2ot has multiple transcription start sites associated with genomic features that indicate regulated expression, including highly conserved elements (HCEs) and chromatin marks characteristic of gene promoters. To identify biological processes in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
242
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(254 citation statements)
references
References 111 publications
10
242
1
1
Order By: Relevance
“…SOX2 is an intronless gene that lies within the third intron of another gene known as SOX2OT [28]. SOX2OT has been proposed to function in the transcriptional regulation of SOX2 [29]. However, its exact biological function has yet remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SOX2 is an intronless gene that lies within the third intron of another gene known as SOX2OT [28]. SOX2OT has been proposed to function in the transcriptional regulation of SOX2 [29]. However, its exact biological function has yet remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in order to identify the biological roles of sox2ot, Amaral et al [29] analyzed the expression pattern of this lncRNA in several developmental systems, in comparison to the expression of sox2. These analyses revealed that sox2ot, similar to sox2, is expressed in mouse ESCs.…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent expression pattern between lncRNA, SOX2OT and SOX2 in certain types of human cancer and human stem cells indicates the possibility that they may be involved in specific similar signaling pathways and engage in co-regulation, which has been validated by some recent studies (15)(16)(17). SOX2OT was postulated to participate in SOX2 transcription, acting as an important enhancer (14). Functionally, the lncRNA, SOX2OT, has a significant role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 86%
“…SOX2OT is an evolutionarily conserved gene that has a high degree of nucleotide identity, with its homologues in mice and other vertebrates (12). The gene does not contain open reading frames, however, it is spliced into several transcripts that are microRNA-like (14). The concurrent expression pattern between lncRNA, SOX2OT and SOX2 in certain types of human cancer and human stem cells indicates the possibility that they may be involved in specific similar signaling pathways and engage in co-regulation, which has been validated by some recent studies (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been increasing evidence that lncRNAs serve crucial biological roles (Mattick 2009). Examples include organism development (Amaral et al 2009;Mattick 2011), imprinting (Zhang et al 2014), epigenetic control (Nakagawa and Kageyama 2014), X inactivation (Froberg et al 2013), and cancer etiology (Yang et al 2014). …”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%